Evaluation of land resilience against natural disasters using ecosystem services approach in Kendari City, Southeast Sulawesi, Indonesia - La Ode Restele; Fitra Saleh; L. M. Iradat; Jufri Karim; Noor Husna Khairisa (Universitas Negeri Malang, 2022)
Kendari City has multiple disasters hazard, especially floods and landslides. Consequently, the city requires systematic preventive efforts to minimize the potential disaster risk. This study aims to create a spatial model to determine the resilience of the land against floods and landslides with an ecosystem services approach. We used Sentinel-2 and DEMNAS (National Digital Elevation Model of Indonesia) as our primary data collection tools. Sentinel-2 was used to compile land use maps, and DEMNAS was the basis for compiling landform maps. The integration of the two was carried out by the analytic hierarchy process (AHP). The results showed that 8,259.98 acres (30.01 percent) of land in Kendari had low resilience to disasters. Those areas are located in a residential area on the TWH (Rocky hill over mixed sedimentary rocks) and KHY (Coalescent estuarine/riverine plain) landforms. The dominant disaster hazard in the area is inundation flooding that occurs almost every year in Kendari. Poor soil infiltration capacity is one factor affecting the area become vulnerable to flooding.